2019
DOI: 10.32598/ijmtfm.v9i3.25706
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Dianthins: A New Promising Horizon Toward Continuous Research on Breast Cancer Bulldozing in Iran

Abstract: The production and secretion of defense proteins are one of the protective mechanisms exploited by plants against pathogens. The production and secretion of defense proteins are one of the protective mechanisms exploited by plants against pathogens. Ribosome-Inactivating Proteins (RIPs), as the main class of these proteins, are considered to facilitate cancer therapy worldwide, because of the potential anticancer activity. Indeed, some of these proteins have cytotoxic and anticancer properties. Extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Induction of Dianthin-30 apoptosis in control samples and concentrations of 1.25, 2.5, 5 and 10 μg/ml on cells in 3D culture increased with increasing dose of toxin were 2, 11.3, 16.7, 19.7 and 7 respectively. However, in 2D culture conditions and the above concentration, this effect was previously reported 6.33, 11.3, 8.3 and 9.6, respectively (1).…”
Section: Comparison Results Of Mtt and Neutral Red Tests With The Res...mentioning
confidence: 67%
See 4 more Smart Citations
“…Induction of Dianthin-30 apoptosis in control samples and concentrations of 1.25, 2.5, 5 and 10 μg/ml on cells in 3D culture increased with increasing dose of toxin were 2, 11.3, 16.7, 19.7 and 7 respectively. However, in 2D culture conditions and the above concentration, this effect was previously reported 6.33, 11.3, 8.3 and 9.6, respectively (1).…”
Section: Comparison Results Of Mtt and Neutral Red Tests With The Res...mentioning
confidence: 67%
“…Also, the results of the neutral red test in this study showed that the inhibitory effect of this toxin on cell growth in the above concentrations was dosedependent and increased. However, in 2D culture conditions at a concentration of 5 μg/ml, this effect was previously reported to be 53.27 (1).…”
Section: Comparison Results Of Mtt and Neutral Red Tests With The Res...mentioning
confidence: 81%
See 3 more Smart Citations